STRATEGI PEMASARAN JERUK DALAM MENGHADAPI PERILAKU KONSUMEN DI MASA PANDEMI COVID-19 (Studi Kasus : Desa Sippan, Kecamatan Pematang Silimahuta, Kabupaten Simalungun) - Bobby Sutrat Saragih; Lyndon Parulian Nainggolan; Fandri Siburian (JURNAL REGIONOMIC, 2022)
This study aims to (1) determine the factors that cause changes in consumer behavior in oranges during the Covid-19 pandemic, (2) determine the attributes that become consumers' decisions to buy citrus fruit products and (3) determine the marketing strategies of traders in order to keep it. survived after the Covid-19 pandemic. The research area was determined purposively or deliberately in Sippan Village, Pematang Silimahuta District, Simalungun Regency, North Sumatra Province. The population in this study were 30 farmers and traders in Saribudolok Market and 30 traders or consumers. The method of determining the sample is carried out by the Accidental method (tracing). To determine the relationship between income, occupation, education, gender, age and number of families on consumer behavior using statistical tests used Chi-Square test with confidence =0.05. To determine the attributes that become the consumer's decision to buy citrus fruit products, Fishbein analysis is used which in principle will calculate Ao (Attitude toward the object). To find out the marketing strategies by traders so that they can survive after the Covid-19 pandemic is done by using a SWOT test. The results showed that gender, education, number of dependents and occupation had no significant effect on changes in consumer behavior during the Covid-19 pandemic, while age and income had a significant effect on changes in consumer behavior during the Covid-19 pandemic. The taste of orange is the main criterion for consumers in forming attitudes towards purchasing oranges. This indicates that consumers prefer lime flavor. Meanwhile, the attributes of price, size and color, which according to consumers are the least important criteria. The marketing strategy based on SWOT analysis is Strength – Opportunity (SO), where the Strength – Opportunity (SO) strategy in the SWOT matrix is first, improving the quality of citrus fruits produced with high prices of oranges and second, namely mutually beneficial cooperation between farmers and traders through media marketing. e-commerce